Challenges in Implementing Contextual Teaching and Learning: A Teacher Perspective Study - Ali, Muttaqin Kholis; Ali, Al Muhtadibillah; Hasanah, Arrahmil (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study examines the challenges faced by teachers in implementing contextual learning at SMA Negeri 1 Tambangan with a focus on the Learning Community aspect. Using a qualitative approach with a descriptive study method, this study involved 30 teachers through in-depth interviews, participatory observations, and document studies. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results reveal significant challenges, including difficulties in creating collaborative learning environments, time constraints, challenges in designing relevant learning tasks, student ability gaps, and barriers to technology integration. Contextual factors such as students' socio-economic backgrounds and community expectations also play important roles. Despite facing challenges, some teachers successfully developed innovative strategies. This research highlights the complexity of implementing contextual learning and the need for a systemic approach in educational reform, involving transformation in teaching practices, school structures, and culture